2019
DOI: 10.3390/plants9010002
|View full text |Cite
|
Sign up to set email alerts
|

Alpha Glucosidase Inhibitory Activities of Plants with Focus on Common Vegetables

Abstract: Type-2 diabetes mellitus is one of the most prevalent metabolic diseases in the world, and is characterized by hyperglycemia (i.e., high levels of glucose in the blood). Alpha-glucosidases are enzymes in the digestive tract that hydrolyze carbohydrates into glucose. One strategy that has been developed to treat type-2 diabetes is inhibition of the activity of alpha-glucosidases using synthetic drugs. However, these inhibitors are usually associated with gastrointestinal side effects. Therefore, the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(92 citation statements)
references
References 82 publications
2
81
0
Order By: Relevance
“…Some studies revealed the presence of α-glucosidase inhibitors in leaves, root, bark, and fruit extracts of various medicinal plants, such as in the leaves extract from Morus alba , mango ( Mangifera indica L.), or in the extract of peel, seeds, pulp, and flakes of jackfruit ( Artocarpus heterophyllus ). Grape seed and green tea extracts have proven to be effective inhibitors of α-glucosidase activity [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies revealed the presence of α-glucosidase inhibitors in leaves, root, bark, and fruit extracts of various medicinal plants, such as in the leaves extract from Morus alba , mango ( Mangifera indica L.), or in the extract of peel, seeds, pulp, and flakes of jackfruit ( Artocarpus heterophyllus ). Grape seed and green tea extracts have proven to be effective inhibitors of α-glucosidase activity [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, since α-glucosidase enzyme is one of the main glycolytic enzymes responsible for digesting carbohydrates in the gastrointestinal tract, α-glucosidase inhibitors are often used as a therapeutic strategy to monitor glucose in diabetics by reducing the intestinal carbohydrate metabolism rate and achieving better glycemic control [ 10 ]. Increasing evidence reveals the presence of α-glucosidase inhibitors in numerous plants, thus motivating researchers to explore several diverse plants as a source of biologically active compounds with hypoglycemic activity [ 11 , 12 , 13 ]. Although antidiabetic drugs have been improved over the past decade, drug resistance is still a major concern to be addressed with effective approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Imino-and aza-sugars are strong inhibitors of the enzyme and are attracting current interest for chaperone therapy of Gaucher disease (Matassini et al, 2020). The trihydroxyl-substituted compound, aminociclitol, (I), is a known -glucosidase inhibitor and is a natural product, being found in several plants (Assefa et al, 2020). The synthesis of (I) can proceed from several key intermediates (Garcia, 2008;Liu & Ma, 2017) and it is this consideration that prompted the structural investigation of the title compound, C 13 H 19 NO 8 , (II).…”
Section: Chemical Contextmentioning
confidence: 99%
“…Mounting evidence indicate that various fruits, vegetables, and whole grains including fermented products, legumes, nuts, green tea, spices, propolis, olive oil, red wine (resveratrol), herbs, and spices are beneficial in T2DM, obesity, and metabolic syndrome due to the presence of non-nutritive secondary metabolites termed as phytochemicals [ 14 , 15 , 16 , 17 , 18 ]. The dietary bioactive phytochemicals play significant role in maintaining health and wellness attributed to their potent pharmacological effects that translate to medicinal benefits [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemicals belong to numerous classes such as polyphenols, terpenoids, flavonoids, alkaloids, sterols, pigments, and unsaturated fatty acids [ 20 ]. Many of the edible plants and phytochemicals are suggested to be useful in T2DM and delay and or prevent complications exerting a pronounced beneficial effect in controlling hyperglycemia due to potent antioxidant and anti-inflammatory effects [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%